Endoscopic Diagnostics in Biomedicine : Instrumentation and Applications. - Sujatha, N. (Biomedical engineering collection., 2019)
Endoscopy has been in practice for many years in diagnostic medicine. From a simple image collection device, the endoscope has grown into an instrument that incorporates multiple imaging modalities to extract structural and functional information from different parts of the human body. Concise, yet comprehensive coverage of various endoscopic forms as provided in this book is expected to help the reader to generate new knowledge in this field.